2008
DOI: 10.1038/sj.bjc.6604661
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of insulin-like growth factor 1 system in early-stage cervical cancer

Abstract: This study was aimed to identify the expression and the correlation of insulin-like growth factor-1 (IGF-1) system and their prognostic impacts in cervical cancer. Seventy-two patients with early-stage cervical cancer were eligible. We obtained the serum levels of total IGF-1 and IGF binding protein-3 (IGFBP-3) by enzyme-linked immunosorbent assay and the expression of IGF-1 receptor (IGF-1R) in cancerous tissue by immuno-fluorescent (IF) stains. The 5-year recurrence-free and overall survival rates were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…Although researchers have reported preclinical and clinical implications of IGF-1 for early stage CC [10,11], studies have not determined a significant correlation between the incidence of CC and DM [12,13]. The impact of DM on OS and cancer-specific mortality of patients with early stage CC has never been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Although researchers have reported preclinical and clinical implications of IGF-1 for early stage CC [10,11], studies have not determined a significant correlation between the incidence of CC and DM [12,13]. The impact of DM on OS and cancer-specific mortality of patients with early stage CC has never been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In early-stage cervical cancer patients, lower IGF-I levels seemed to be associated with worse overall survival rate, but was not of an independent value, and there was no relationship between IGFBP-3 levels and survival (Huang et al, 2008).…”
Section: Serum Levels Of Igfs As Cervical Cancer Biomarkersmentioning
confidence: 94%
“…Authors found that high-grade expression of IGF-IR, is an independent predictor of cervical cancer death and recurrence, and when combined with elevated squamous cervical cancer antigen (SCC Ag) serum level, could further help identify the subgroup of patients at higher death risk. Colocalisation of IGF-I and IGF-IR in the cancerous tissues, and the lack of correlation between circulating IGF-I or IGFBP-3, and IGF-IR overexpression in cervical cancer tissue, give support to a paracrine or autocrine function of the IGF system in early-stage cervical cancer, with the corresponding adverse IGF-I stimulation of IGF-IR signaling (Huang et al, 2008).…”
Section: Tissue Expression Of Igfs As Risk or Prognosis Biomarkers Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohlsson et al 17 suggested a revision in the classical somatomedin hypothesis and proposed the "dual somatomedin hypothesis" in which autocrine/ paracrine igf-1 is the main determinant of postnatal body growth, and liver-derived endocrine-acting igf-1 supplies negative feedback to gh secretion and possibly exerts other effects on carbohydrate and lipid metabolism. Paracrine/autocrine igf-1 promotes the growth of many cancers, such as acute myeloid leukemia 18 , chronic myelogenous leukemia 19 , neuroendocrine tumour 20 , breast cancer 21 , and cervical cancer 22 . Pulmonary neuroendocrine tumours such as carcinoids can produce ectopic gh in sufficient quantities to manifest as acromegaly, potentially contributing to local and distant igf activation loops 23 .…”
Section: Discussionmentioning
confidence: 99%